Corporate Ownership and Sustainability Reporting: Environmental Agencies’ Moderating Effects - Haladu, Alhassan; Salim, Basariah Bt. (International Journal of Economics and Financial Issues, 2016)
In third world economies like Nigeria, the role of foreign ownership of businesses compared to local ownership on environmental issues has been given very little attention. Foreign investors may assist in the fight against environmental degradation. This research determines the relationship between environmental information disclosure and ownership structure in combination with environmental agencies using the latest version of GRI (G4). The study is a pioneer application of environmental agencies’ role in sustainability reporting and considers 81 companies in 6 environmentally sensitive industries of the economy. From a stratified random selected sample of 67 firms, the study tested for the relationship from 2009 to 2014. The outcome showed an inverse and significant relationship between environmental disclosure and ownership structure. This forced the recommendation that local ownership should be encouraged to grow at a faster rate so that a positive impact will be reflected on environmental information disclosure. Keywords: Corporate Ownership Structure, Environmental Disclosure, Environmental Agencies JEL Classifications: G31, H23, R11